Kratom (Mitragynine) Ingestion Requiring Naloxone Reversal - Overbeek, Daniel L. (Clin Pract Cases Emerg Med, 2019)
Kratom (mitragynine) is a naturally occurring opioid agonist whose use has been escalating. Its suppliers advertise it as a safe alternative for opioids and a safe treatment for opioid-withdrawal symptoms. There has been controversy in the past two years regarding the legal status and lack of regulation surrounding kratom. Currently, kratom is legal and unregulated, leaving users at risk from unpredictable potencies and effects. We present the first case of successful naloxone reversal of opioid toxidrome from recreationally used kratom. We advocate further research and regulation to ensure standardized dosing to protect patients.